2016 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2016
DOI: 10.1109/icassp.2016.7472274
|View full text |Cite
|
Sign up to set email alerts
|

Compressive sensing based target counting and localization exploiting joint sparsity

Abstract: One of the fundamental issues in Wireless Sensor Networks (WSN) is to count and localize multiple targets accurately. In this context, there has been an increasing interest in the literature in using Compressive Sensing (CS) based techniques by exploiting the sparse nature of spatially distributed targets within the monitored area. However, most existing works aim to count and localize the sparse targets utilizing a Single Measurement Vector (SMV) model. In this paper, we consider the problem of counting and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 28 publications
0
18
0
1
Order By: Relevance
“…Also, the state-of-art recovery algorithm is applied to compare with the Ges-DFL algorithm, including Temporally Sparse Bayesian Learning (TSBL) [32], Multiple-Focal Underdetermined System Solver (M-FOCUSS) [33], Multiple Greedy Marching Pursuit (MGMP) [34], Simultaneous Orthogonal Marching Pursuit SOMP [35] and Variational Bayesian Expect-Mean (VBEM) [31].…”
Section: A the Simulation Performancementioning
confidence: 99%
“…Also, the state-of-art recovery algorithm is applied to compare with the Ges-DFL algorithm, including Temporally Sparse Bayesian Learning (TSBL) [32], Multiple-Focal Underdetermined System Solver (M-FOCUSS) [33], Multiple Greedy Marching Pursuit (MGMP) [34], Simultaneous Orthogonal Marching Pursuit SOMP [35] and Variational Bayesian Expect-Mean (VBEM) [31].…”
Section: A the Simulation Performancementioning
confidence: 99%
“…The research in [31] considered the same problem in a novel two-dimensional framework, where RSS samples are compressed in the space domain and the location information is compressed in the time domain. By exploiting the joint sparsity feature of the target location, the multiple measurement vectors model was adopted to tackle the time-varying environment [32]. In [33], a multi-channel indoor localization approach was proposed to overcome the channel mismatch problem and the matrix completion theory was adopted to reduce the training workload.…”
Section: B Compressive Sensing Based Localizationmentioning
confidence: 99%
“…Additionally, when multiple targets are simultaneously active, signals transmitted by targets are overlapped at each sensor. To this end, as in [8], [28], [32], [36]- [38], we further assume that the strengths of targets will be linearly superimposed without any interaction between them. For instance, as shown in Fig.…”
Section: A Signal Modelmentioning
confidence: 99%
“…The contribution in [157] proposed a CS-based approach for sparse target counting and positioning in wireless sensor networks by employing a novel Greedy Matching pursuit (GMP) algorithm. Recently, authors in [158] studied the problem of target counting and localization by exploiting the joint sparsity feature of an MMV model and demonstrated that the performance of the proposed MMV approach is superior than that of the conventional single measurement vector method in terms of target counting and localization accuracies.…”
Section: B Related Literaturementioning
confidence: 99%